ANTHOCYANIN AND ANTHOCYANIDIN CONTENT OF HIGHBUSH BLUEBERRIES CULTIVATED IN BRAZIL - SARKIS, JÚLIA RIBEIRO; TESSARO, ISABEL CRISTINA; FERREIRA MAECZAK, LIGIA DAMASCENO (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2013)
The objective of this study was to apply a HPLC methodology for qualitative and quantitative analysis of the six anthocyanidins present in fruits and to analyze the anthocyanin and anthocyanidin content of blueberries cultivated in Southern Brazil. The samples used belong to highbush blueberries (Vaccinium corymbosum) cultivars. Total anthocyanin content was determined by the pH differential method and an HPLC gradient elution system with C18 column and UV-Vis detection at 520 nm were used for separation and quantification of the anthocyanidins. Total anthocyanin content was of 128 ± 3 mg per 100 g of fresh pulp. Blueberry pulp presented 55 % of delphinidin, 8 % of cyanidin, 3 % of peonidin and 34 % of malvidin. Pelargonidin was not identified in the sample and petunidin was below the limits of quantification. The results were similar to those reported in studies using North American and European blueberries.